2003
DOI: 10.1590/s0100-879x2003001100014
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of recombinant human erythropoietin in pharmaceutical products

Abstract: The potencies of mammalian cell-derived recombinant human erythropoietin pharmaceutical preparations, from a total of five manufacturers, were assessed by in vivo bioassay using standardized protocols. Eight-week-old normocythemic mice received a single subcutaneous injection followed by blood sampling 96 h later or multiple daily injections with blood sampling 24 h after the last injection. Reticulocyte counting by microscopic examination was employed as the endpoint using the brilliant cresyl blue or selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…In the second functional model, EPO, a potent erythropoietic agent that signals exclusively through the JAK-2 pathway (9), was used to induce reticulocytosis in the peripheral blood of mice (32). The effect of the JAK-3 inhibitors, WYE-151650 and CP-690,550, on EPO-induced reticulocytosis was assessed as a measure of JAK-2 selectivity in vivo.…”
Section: In Vitro Activity Wye-151650 (mentioning
confidence: 99%
“…In the second functional model, EPO, a potent erythropoietic agent that signals exclusively through the JAK-2 pathway (9), was used to induce reticulocytosis in the peripheral blood of mice (32). The effect of the JAK-3 inhibitors, WYE-151650 and CP-690,550, on EPO-induced reticulocytosis was assessed as a measure of JAK-2 selectivity in vivo.…”
Section: In Vitro Activity Wye-151650 (mentioning
confidence: 99%
“…26,27 ) Different commercially produced follow-on epoetin alpha products share an identical amino acid sequence, but differ greatly in their glycosylation profiles, and hence in their biological activity. 28 These differences can be dramatic: one study using isoelectric focusing to compare 11 epoetin alpha products from manufacturers in Korea, Argentina, China and India found that their molecular weights varied substantially (figure 3). 29 Additional studies have reported that epoetins from different sources vary widely in biological activity from 70% to over 200% of their own stated specifications.…”
Section: Pharmacokinetics Of Biphasic Insulinmentioning
confidence: 99%
“…Since the manufacturers of biopharmaceuticals are not obliged to disclose their manufacturing procedures, biosimilars manufacturers have to work out their own manufacturing protocols based upon the final product. When analytic and clinical evaluations of EPO biosimilar products currently marketed outside the US and Europe were conducted, it was revealed that the products' composition differed widely, they exhibited interbatch variation, and often did not meet selfdeclared specifications [11,12]. This variation between products underscores the colossal difficulties in replicating biopharmaceutical proteins.…”
Section: Biopharmaceuticals: the Manufacturing Challengementioning
confidence: 99%